2006
DOI: 10.1097/01.pdm.0000213461.53021.84
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Mutation Analysis in Fine Needle Aspiration (FNA) Cytology of the Thyroid

Abstract: BRAF mutations have been detected in 30% to 80% of papillary thyroid carcinomas (PTC). Several detection methods for BRAF mutation have been reported, but a direct comparison between different assay methods has not been previously reported. In this study, we examined the diagnostic utility of BRAF (T1799A) mutation in 71 cases of thyroid fine needle aspiration specimens using 4 different methods, including direct sequencing, Colorimetric Mutector Assay, real-time LightCycler polymerase chain reaction (LC PCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
3
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 31 publications
1
77
3
8
Order By: Relevance
“…As reported by Jin et al 35 for BRAF p.V600E mutation, the choice of four different approaches (direct sequencing, the colorimetric TrimGen Mutector assay, PCR with FRET probes, and PCR with SYBR Green) does not significantly affect the molecular diagnosis, and the choice of the best test depends mainly on the laboratory expertise and available financial and technical resources.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Jin et al 35 for BRAF p.V600E mutation, the choice of four different approaches (direct sequencing, the colorimetric TrimGen Mutector assay, PCR with FRET probes, and PCR with SYBR Green) does not significantly affect the molecular diagnosis, and the choice of the best test depends mainly on the laboratory expertise and available financial and technical resources.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction and direct forward and reverse sequencing of the BRAF gene were performed on formalin-fixed paraffinembedded tissue as described previously. 19,24,25 …”
Section: Methodsmentioning
confidence: 99%
“…This variability may have introduced inconsistencies in the results of BRAF mutation testing. Although we performed BRAF mutation analysis with both FNAB specimens and surgical specimens, numerous studies have demonstrated that BRAF mutation analysis can be performed readily and reliably using solely FNAB specimens preoperatively (Chung et al 2006, Jin et al 2006). In conclusion, BRAF mutation was significantly less frequent in conventional PTC patients with CLT.…”
Section: Discussionmentioning
confidence: 99%